Technology Entrepreneurship Project (ENT 600) : Philips Malaysia / Muhammad Syafiq Mohd Fahizal - Mohd Fahizal, Muhammad Syafiq (2021)
Koninklijke Philips N.V. (literally Royal Philips, commonly shortened to Philips, stylized in its logo as PHILIPS) is a Dutch multinational conglomerate corporation that was founded in Eindhoven. Since 1997, it has been mostly headquartered in Amsterdam, though the Benelux headquarters is still in Eindhoven. Philips was formerly one of the largest electronics companies in the world, currently focused in the area of health technology, with other divisions being divested. It was founded in 1891 by Gerard Philips and his father Frederik, with their first products being light bulbs. It currently employs around 74,000 people across 100 countries. The company gained its royal honorary title in 1998 and dropped the "Electronics" in its name in 2013, due to its refocusing from consumer electronics to healthcare technology. Earphones have a smaller design than headphones or headsets. Especially for speaker size. If the headphones or headset cover all or part of the ear, these earphones only cover the ear canal. Earphones are often an additional accessory when buying a smartphone. Today, earphones continue to grow, not only using 3.5 mm audio cables and jacks, but now they support wireless with Bluetooth and TWS (True Wireless Stereo) technology. Despite its small size, the earphones are supported by a microphone hole for communication. The sound produced is not as good as the headset. In addition, wired and wireless earphones are usually equipped with ups and downs, as well as multifunction buttons to take phone calls as well as to control the music player. Philips earphones use a variety of modern technologies. This can create a sophisticated environment. This Philips product is an example for some other products. It has also attracted users to use this. Some technologies that are not available on other brand earphones already exist in these Philips earphones.